Maternal psychosocial risk factors and lower respiratory tract infection (LRTI) during infancy in a South African birth cohort. - Rae MacGinty; Maia Lesosky; Whitney Barnett; Polite M Nduru; Aneesa Vanker; Dan J Stein; Heather J Zar (PLoS ONE)
Objective To investigate the association between maternal antenatal and/or postnatal psychosocial risk factors (including depression, psychological distress, alcohol abuse and intimate partner violence (IPV) and infant lower respiratory tract infection (LRTI) in a low- and middle-income-country (LMIC). Study design Pregnant women (n = 1137) enrolled in a South African birth cohort study, the Drakenstein Child Health Study (DCHS) were longitudinally assessed for psychosocial risk factors including depression, psychological distress, alcohol abuse and/or intimate partner violence (IPV). Infants were followed from birth until one year of age for the development of LRTI by active surveillance. Two outcomes were evaluated: any LRTI, and severe and/or hospitalised LRTI. Logistic regression was used to identify associations between individual maternal psychosocial risk factors and LRTI outcomes. Analyses stratified by age were also performed to determine which age groups related to infant LRTI were linked with maternal psychosocial risk factors. Results There were 606 LRTI episodes in 369 infants in the first year (crude incidence rate = 0.53 episodes per person-year, 95%CI: 0.50; 0.56); 31% (n = 186) of episodes were severe or hospitalised events. Maternal psychosocial risk factors were associated with LRTI and severe LRTI, particularly postnatal and long-term maternal psychological distress, antenatal maternal alcohol consumption, and postnatal maternal IPV. Age stratified analyses found that antenatal maternal alcohol consumption was associated with early infant LRTI, while antenatal maternal depression was linked with infant severe LRTI between 3 and 6 months of age, and postnatal maternal IPV was associated with early LRTI and severe forms of LRTI. Conclusion The associations between maternal psychosocial risk factors and infant LRTI highlight the potential value of screening for maternal psychosocial risk factors in clinical settings and developing targeted interventions. Such interventions may not only improve maternal well-being, but also help reduce the burden of infant LRTI in LMIC settings.